Managerial Perspectives on the Impact of HRD Programs and Psychological Empowerment on Employees’ Innovation Behavior and Performance in Developing Economies - Adhikari, Yogendra (New Perspective: Journal of Business and Economics, 2025)
Enhancing employee performance is a critical priority for organizations globally. Effective human resource management is essential for fostering employees’ efficiency, productivity, empowerment, and innovativeness, which together contribute to superior organizational performance. This study explores the impact of Human Resource Development (HRD) and empowerment initiatives on employee innovativeness and performance from the perspective of managers, with a specific focus on organizations in developing economies. Employing a pooled qualitative analysis, the research involved in-depth interviews with executive-level managers from four organizations in Nepal across the banking, insurance, and hotel sectors. Data were transcribed and coded using the QDA Miner software, with thematic analysis based on key constructs such as HRD, Psychological Empowerment, Innovative Behavior, and Employee Performance. Findings highlight the effective implementation of HRD practices and empowerment initiatives as critical drivers of employees' innovative behaviors and overall performance. The managers’ insights provide valuable understanding of these dynamics within the context of developing economies. The study underscores the essential role of HRD and empowerment tools in enhancing organizational success by fostering employee innovativeness and high performance, particularly in developing country settings such as Nepal.